2017
DOI: 10.3727/096368916x692951
|View full text |Cite
|
Sign up to set email alerts
|

A Nerve Conduit Containing a Vascular Bundle and Implanted with Bone Marrow Stromal Cells and Decellularized Allogenic Nerve Matrix

Abstract: Cells, scaffolds, growth factors, and vascularity are essential for nerve regeneration. Previously, we reported that the insertion of a vascular bundle and the implantation of bone marrow-derived mesenchymal stem cells (BM-MSCs) into a nerve conduit promoted peripheral nerve regeneration. In this study, the efficacy of nerve conduits containing a vascular bundle, BM-MSCs, and thermally decellularized allogenic nerve matrix (DANM) was investigated using a rat sciatic nerve model with a 20-mm defect. Lewis rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 47 publications
0
54
0
2
Order By: Relevance
“…Fifth, the size mismatch between the diameter of the conduit and the sciatic nerve should be discussed. We decided to use the diameter of the bio 3D conduit from previous studies, which was larger than that of the sciatic nerve (Kaizawa et al, ; Yurie et al, ). However, a narrower conduit was used in other studies (Kim, Lee, Jeon, et al, ; Mohammadi, Shokrzadeh, & Maroufi, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, the size mismatch between the diameter of the conduit and the sciatic nerve should be discussed. We decided to use the diameter of the bio 3D conduit from previous studies, which was larger than that of the sciatic nerve (Kaizawa et al, ; Yurie et al, ). However, a narrower conduit was used in other studies (Kim, Lee, Jeon, et al, ; Mohammadi, Shokrzadeh, & Maroufi, ).…”
Section: Discussionmentioning
confidence: 99%
“…In tissue engineering, cells, scaffolds, and growth factors are considered to be essential elements for promoting regeneration (Kaizawa, Kakinoki, Ikeguchi, et al, 2016;Widgerow, Salibian, Kohan, et al, 2014). Several researchers have reported that administration of stem cells or biologically active molecules into artificial scaffolds enhances the regenerative potential (Eren et al, 2016;Kaizawa et al, 2016;Kaizawa, Kakinoki, Ikeguchi, et al, 2017). However, when using artificial scaffolds, problems related to biocompatibility induced by a foreign body reaction are inherent risks.…”
Section: Discussionmentioning
confidence: 99%
“…An ideal nerve conduit should support recellularization because the seeding of the cells into nerve conduit has been shown to be essential in promoting nerve regeneration (Kaizawa et al 2017(Kaizawa et al , 2016Shalaby et al 2017;Xu et al 2016). To test whether decellularized HUC artery conduit support recellularization, mesenchymal stem cells and neurodifferentiated mesenchymal stem cells (ndMSCs) were seeded into the luminal surface of the decellularized HUC artery and incubated for 2 days.…”
Section: In Vitro Evaluation Of Constructed Nerve Conduit (Pre-grafting)mentioning
confidence: 99%
“…It was estimated that 50000 procedures were performed annually to repair damaged peripheral nerves at the cost of USD 7 billion per year (Liao et al 2013). Despite rapid clinical advancement, the treatment of PNI is still a challenge especially in critical gap (greater than 3 cm) (Kaizawa et al 2017;Liao et al 2013). This condition is worsened by the limited regeneration of peripheral nerve that depends on several factors including the length of injury, presence of neurotrophic factors and Schwann cells (Höke 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there is a growing interest in the clinical potential of mesenchymal stem cells derived from bone marrow (Kaizawa et al, 2017), adipose tissue (Kappos et al, 2015;Saller et al, 2018), and menstrual blood (Farzamfar et al, 2017). Among these, bone marrow stem cells are reported to enhance neovascularization by producing angiopoietin-1 and 2 (Yang, Cai, Xu, Xu, & Liang, 2015).…”
Section: Figure 12mentioning
confidence: 99%